“To think of your happy fireside”: The Materiality of Home and Belonging in the Letters of James and Letitia Hargrave, 1826–1854 - Bell, Elyse (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2019)
The concept of “home” can refer to a range of things, from a house or a homeland, to family and community, or even a feeling of belonging or exclusion. This paper asks what home meant for employees of the Hudson’s Bay Company and their families by taking HBC employee James Hargrave and his wife Letitia as a case study, examining the different ways they conceived of home in the letters that they wrote to their families in Lower Canada and Britain, and to each other, between 1826 and 1854. Home had multiple meanings for the Hargraves, which changed over time depending on their location and circumstances. The unsettled nature of life in the fur trade, and the uncertain future it held for them, led to a sense of anxiety. The Hargraves found comfort in ideas of home that were grounded in connections to their homeland, their family and community in Scotland and Lower Canada, and eventually the family that they created for themselves. Home also had very material connotations, and was entangled with the memories, experiences, and imaginings of people, places and things, from James Hargrave picturing himself seated by his father’s fireside, to Letitia Hargrave cherishing jars of marmalade sent from Scotland by her mother. Thinking about the materiality of the past when examining the Hargraves’ letters reveals some of the strategies that they employed to reinforce their connections to family and friends, and how these relationships created and maintained a sense of home and belonging.